TRADISI BOBOK BUMBUNG SEBAGAI UPAYA MEMBANGUN KARAKTER SISWA BERPRINSIP PANCASILA - Saputri, Ines Ika (PUSAT MPK UNIVERSITAS BRAWIJAYA, 2024)
Technological disruption needs to be accompanied by character formation based on Pancasila principles so that the younger generation is able to protect themselves from the negative impacts it causes. One of the efforts is through local wisdom, as is done by the Pesanggrahan village community with the bobok bumbung tradition. This research aims to determine the procession and efforts to build a character with Pancasila principles through the bobok bumbung tradition. Researchers used qualitative descriptive methods. The techniques and instruments in this research are observation analysis, interview guidelines, and documentation in the form of photos. The informants for the interviews selected in this research were village officials, village elders, and students of SMP Negeri 3 Kroya who follow this tradition. The validation used in this research is the triangulation technique. The results of this research show that the traditional Bobok Tubung procession is carried out with traditional arts performances and competitions. Character formation based on creative character values, caring for nature, and a clean lifestyle, is realized through art performances, coloring competitions, and fashion shows. Responsible character, love for the homeland, togetherness, discipline, agility, and resilience through traditional arts. The formation of caring, cooperative, and patriotic characters is realized through the puppet show Pandawa Syukur. There is a need to preserve and develop this tradition. Further research needs to be conducted, so that we can find out the extent of the success of character formation with Pancasila principles through the bobok bumbung tradition.